Long-Term Residence Permit in the Czech Republic, Slovak Republic and the Republic of Poland - Bednářová, Markéta; Lásková, Eva (Studia Prawa Publicznego, 2020)
In all three Central European countries, long-term residence is defined as residence for a specific purpose of more than 90 days. The requirements for granting this type of residence are generally similar with differences in the individual types of purpose of this residence permit. The Polish Act contains a category that could be defined as ‘above-framework’, expanding the range of options that make it possible to obtain long-term residence. The Slovak legislation contains the purpose of “special activities”. In comparison with the Czech legislation, the range of possibilities for obtaining long-term residence in Slovakia is more extensive and less rigid. Specifically, in the case of long-term residence for the purpose of study, there is a fundamental difference in the legislation in the Czech Republic and Slovak Republic, where Slovak legislators include in the term “study” all university, secondary, and higher vocational education. The Polish Act mentions only university studies and doctoral studies. The administration related to the admission of a foreign student to a specific school in the territory is certainly more extensive and demanding in Poland, with both the minister and the voivode enter the process beyond the framework of standard state administration bodies. The arrangement of the Act reveals a fundamental difference in Poland, where the sequence and logic of the arrangement is different to the Czech or Slovak legislation, which is expressed in which institutions Poland focus greater attention and emphasis or importance. None of the countries completely leaves the issue of visas for aliens from third countries unregulated. Although the legislation is identical in many respects, there are differences between individual institutions and the periods for which a visa can be issued. However, the issue of alien law is, at first sight, very extensive and content-intensive in all the above Central European countries, as evidenced by the length of the legislation itself, the complexity of individual institutions, and specific complexity of the provisions.